2018
DOI: 10.1021/acs.macromol.8b00419
|View full text |Cite
|
Sign up to set email alerts
|

A Planar Cyclopentadithiophene–Benzothiadiazole-Based Copolymer with sp2-Hybridized Bis(alkylsulfanyl)methylene Substituents for Organic Thermoelectric Devices

Abstract: A semicrystalline p-type thermoelectric conjugated polymer based on a polymer backbone of cyclopentadithiophene and benzothiadiazole, poly­[(4,4′-(bis­(hexyldecyl­sulfanyl)­methylene)­cyclopenta­[2,1-b:3,4-b′]­dithiophene)-alt-(benzo­[c]­[1,2,5]­thiadiazole)] (PCPDTSBT), is designed and synthesized by replacing normal alkyl side-chains with bis­(alkylsulfanyl)­methylene substituents. The sp2-hybridized olefinic bis­(alkylsulfanyl)­methylene side-chains and the sulfur–sulfur (S–S) chalcogen interactions extend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 45 publications
0
65
0
Order By: Relevance
“…[6,17] For this reason, it has been widely used in various fields of organic devices including organic field-effect transistors, [6,18] solar cells, [19][20][21] light-emitting diodes, [3] sensors, [22] and TE devices. [23] The fundamental principle of doping with BCF is known to be based on the Lewis acid-base interaction that induces the frontier orbital hybridization between the Lewis acidic boron atom and the Lewis basic nitrogen or sulfur atoms in conjugated polymers. [17,18,24] This process involves the formation of charge transfer complexes, which generally leads to the inefficient partial charge transfer mechanism; [5] in this process, the charge carrier transfer between the neat polymer and the complex can somehow occur but their mismatched energy levels make the transfer much less efficient compared to the direct integer charge transfer between the neat polymer and the dopant (i.e., ion-pair formation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,17] For this reason, it has been widely used in various fields of organic devices including organic field-effect transistors, [6,18] solar cells, [19][20][21] light-emitting diodes, [3] sensors, [22] and TE devices. [23] The fundamental principle of doping with BCF is known to be based on the Lewis acid-base interaction that induces the frontier orbital hybridization between the Lewis acidic boron atom and the Lewis basic nitrogen or sulfur atoms in conjugated polymers. [17,18,24] This process involves the formation of charge transfer complexes, which generally leads to the inefficient partial charge transfer mechanism; [5] in this process, the charge carrier transfer between the neat polymer and the complex can somehow occur but their mismatched energy levels make the transfer much less efficient compared to the direct integer charge transfer between the neat polymer and the dopant (i.e., ion-pair formation).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, considering that the BCF-water complex is known to be a stronger Brønsted acid than even HCl in some solvents (e.g., acetonitrile), [27] we believe that it has great potential to dope conjugated polymers for TE applications. However, research on BCF has mostly focused on its Lewis acidic properties, [6,[17][18][19][20][21]23,24,28] and Brønsted acidic properties of BCF-water complexes have not yet been studied in depth.…”
Section: Introductionmentioning
confidence: 99%
“…These organic TMs demonstrated advantages for assembling flexible TEG devices, but their low Seebeck coefficient and low electrical conductivity resulted in poor ZT values as well as lower power factors than those of inorganic TMs, which limits their applications. To improve their thermoelectric properties, efforts were made to increase these polymers' conductivity by doping, dedoping, and implementing a hybrid with high conductive carbon/metal materials . For instance, Kim et al reported that the dimethyl sulfoxide (DMSO) doped PEDOT:PSS derived a maximum polymer ZT value of 0.42 at room temperature .…”
Section: Materials For Energy Conversion Devicesmentioning
confidence: 99%
“…The efficiency with which a material converts a thermal gradient to electrical energy depends on the figure of merit ( ZT = S 2 σT /κ), where S , σ, T , and κ are Seebeck coefficient, electrical conductivity, absolute temperature, and thermal conductivity, respectively . As the carrier concentration ( n ) increases, typically, σ and κ increase and S decreases . Thus, to obtain high ZT , it is essential to optimize the parameters correlated to the n of the material …”
mentioning
confidence: 99%
“…Present TE materials are usually comprising inorganic semi‐metallic alloy such as Bi 2 Te 3 , PbTe, and Sb 2 Te 3 ; however, practical application has rather limited because of their expensiveness and high toxicity . In contrast, organic thermoelectric (OTE) materials represent many advantages, such as light weight, low pollution, and adjustable molecular structure.…”
mentioning
confidence: 99%